MEAN BUSINESS : HOW I SAVE BAD COMPANIES AND MAKE GOOD COMPANIES GREAT - Dunlap, Albert J. (Albert John), 1937-2019, author 640400; Andelman, Bob, author 640402 (New York : Simon & Schuster, 1997)
pt. 1. Saving a fallen giant -- Paper thin: a microcosm of bad business -- Shock therapy -- pt. 2. Four simple rules -- Rule 1: get the right management team -- Rule 2: pinch pennies -- Rule 3: know what bysiness you're in -- Rule 4: get a real strategy -- pt. 3. Who I am and where I come from -- "A nothing kid from Hoboken" -- Rambo in pinstripes (aka "Chainsaw Al") -- pt. 4. Dunlapping the corporation -- Look under "M" for marketing -- Fire all the cunsultants -- Real jobs, real cuts -- The best bargain is an expensive CEO -- Whose company is it, anyhow? -- Board of directors, God forgive them -- Feed a company, starve a culture -- Impressing the analysts -- Now there's a bright idea -- Fighting words.